Kenaf Biochar as an Eco-Friendly Adsorbent for Removal of Cu(II) and Pb(II): Optimal Temperature, Adsorption Models, and Efficiency Evaluation - Choi, Moon Yeong; Lee, Chang Gu; Yoon, Young Man; Park, Seong Jik (Applied Organometallic Chemistry, 2024)
This study examined the adsorption capacities of biochars derived from kenaf (KF-BCs) for the removal of heavy metals such as Cu(II) and Pb(II). The thermal decomposition temperature (300–750°C) significantly influenced the morphology and composition of KF-BCs, enhancing their surface area, pore structure, and alkalinity. Among them, kenaf pyrolyzed at 750°C (KF-750) was the most effective in removing Cu(II) and Pb(II), as validated by kinetic, equilibrium, and isotherm model analyses. Adsorption kinetics revealed that equilibrium was attained after 24 h, with chemisorption governing the process rate. Equilibrium adsorption conformed to the Langmuir and Freundlich models for Cu(II) and Pb(II), respectively. KF-750 exhibited midrange adsorption capacities for Cu(II) and Pb(II) (23.47 ± 0.3 mg/g and 50.07 ± 0.9 mg/g, respectively), compared with the literature. The thermodynamic assessment revealed an endothermic process with positive ∆H0, indicating that higher temperatures favor metal adsorption. At low pH, adsorption decreased due to electrostatic repulsion, particularly affecting Cu(II). More than 99.8% of Cu(II) and Pb(II) were removed with a 5.00 g/L KF-750 dose. The cation effect order on KF-750 was Ca2+ > Mg2+ > Na+ > K+. Overall, KF-750 demonstrates promising potential as an adsorbent for the efficient heavy metal removal from aqueous solutions, presenting a viable option for environmental remediation.
Keywords: Adsorbent dose; Adsorption capacities; Adsorption modeling; Biochar; Carbonaceous materials; Competing cation; Eco-friendly; Optimal temperature; Pyrolysis temperature; Solution pH; adsorbent dose; carbonaceous material; competing cations; pyrolysis temperature; solution pH; wastewater treatment